Silent hypoxemia in a patient with severe SARS-CoV-2 pneumonia - A. D. Palman; D. A. Andreev; S. A. Suchkova (Сеченовский вестник)
Patients with COVID-19 are typically characterized by severe lung injury with the development of acute respiratory failure. However, in some patients, subjective well-being may remain relatively satisfactory for a long time and, despite severe hypoxemia, they do not complain of shortness of breath. Case report. We observed a 65-year-old man hospitalized with severe SARS-CoV-2 pneumonia, low level of blood oxygen saturation, but at the same time without complaints of shortness of breath. Only as the disease progressed with a decrease in oxygen saturation when breathing atmospheric air (SpO2 ) lower than 85% he began to notice a feeling of lack of air. The patient’s condition worsened and as a result, he died in the intensive care unit from multiple organ failure. Discussion. This case clearly illustrates one more feature of the course of pneumonia associated with the novel SARSCoV-2 coronavirus and shows that SpO2 measurement is one of the leading objective criterion that allows a doctor to assess the real severity of a patient’s condition with COVID-19.